2019
DOI: 10.1038/s41598-019-56098-3
|View full text |Cite
|
Sign up to set email alerts
|

The local immune response during Echinococcus granulosus growth in a quantitative hepatic experimental model

Abstract: The local immune mechanisms responsible for the establishment and development of Echinococcus granulosus sensu stricto infection in the liver, have been little explored. We developed a suitable experimental model that mimics naturally infected livers using portal injection of protoscoleces. Opposite to Echinococcus multilocularis infection which is dose-dependent, fully mature hydatid cysts can be established in the liver whatever the injection dose; although most of the infection sites were seen at the establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Cystic echinococcosis (CE), also known as hydatid disease, is a worldwide chronic parasitic disease, threatening the health of livestock and humans [ 1 ]. Humans are exposed to the eggs of Echinococcus granulosus after close contact with infected livestock or contaminated food [ 2 , 3 ]. At present, diagnosis of human echinococcosis relies mainly on imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystic echinococcosis (CE), also known as hydatid disease, is a worldwide chronic parasitic disease, threatening the health of livestock and humans [ 1 ]. Humans are exposed to the eggs of Echinococcus granulosus after close contact with infected livestock or contaminated food [ 2 , 3 ]. At present, diagnosis of human echinococcosis relies mainly on imaging techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The life of the pathogen in the human body is relatively long, ranging from 1 to 30 years, and the symptoms of the initial infection are not obvious. Therefore, it is difficult to diagnose, treat, and control [ 2 , 4 , 5 ]. Due to the limitations of current diagnostic and therapeutic measures, numerous studies have been carried out in the field of immunology associated with E. granulosus infection in the hope of developing vaccines [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Echinococcal disease has never been described as a cause of secondary ITP. Recent data have shown that ITP may be associated with complement activation [ 14 ], and that complement activating anti-Echinococcus specific antibodies may be found in echinococcosis [ 15 ]. There has however been no published case report or in vitro study on the association between thrombocytopenia and echinococcosis in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Background CE, also named hydatid disease, is a worldwide chronic parasitic disease, threatening the health of livestock and humans [1]. Human beings are exposed to the eggs of E. granulosus after close contact with infected livestock or contaminated food [2,3]. At present, diagnosis of human echinococcosis mainly dependent on imaging techniques.…”
mentioning
confidence: 99%
“…The pathogen in the human body is relatively long, ranging from 1 to 30 years and the symptoms of the initial infection is not obvious. So, it is hard to diagnose, treat, and control [4][5][6]. Due to the limitations of current diagnostic and therapeutic measures, a mass of research has been done in the eld of immunology associated with E. granulosus infection in the hope of developing future vaccines [7,8].…”
mentioning
confidence: 99%